Morphology and function of cryopreserved whole ovine ovaries after heterotopic autotransplantation - Sharma Rakesh K; Bilski Jerzy J; Borowczyk Ewa; Yazici Ilker; Banerjee Jashoman; Grazul-Bilska Anna T; Siemionow Maria; Falcone Tommaso (BMC, 2008)
Abstract Background The objective of this study was to perform complex characterization of cryopreserved and then autotransplanted ovaries including determination of the ability to respond to in vivo follicle stimulating hormone (FSH)-treatment, fertilizability of retrieved oocytes, and morphology, vascularization, cellular proliferation and apoptosis in sheep. Methods Mature crossbred ewes were divided into two groups; an intact (control) group (n = 4), and autotransplanted group (n = 4) in which oophorectomy was performed laparoscopically and ovaries with intact vascular pedicles frozen, thawed and transplanted back into the same animal at a different site. Approximately five months after autotransplantation, estrus was synchronized, ewes were treated with FSH, and ovaries were collected. For all ovaries, number of visible follicles was determined, and collected cumulus oocyte complexes (COC) were matured and fertilized in vitro. Remaining ovarian tissues were fixed for evaluation of morphology, expression of factor VIII (marker of endothelial cells), vascular endothelial growth factor (VEGF; expressed by pericytes and smooth muscle cells), and smooth muscle cell actin (SMCA; marker of pericytes and smooth muscle cells), and cellular proliferation and apoptosis. Two fully functional ovaries were collected from each control ewe (total 8 ovaries). Results Out of eight autotransplanted ovaries, a total of two ovaries with developing follicles were found. Control ewes had 10.6 +/- 2.7 follicles/ovary, oocytes were in vitro fertilized and developed to the blastocyst stage. One autotransplanted ewe had 4 visible follicles from which 3 COC were collected, but none of them was fertilized. The morphology of autotransplanted and control ovaries was similar. In control and autotransplanted ovaries, primordial, primary, secondary, antral and preovulatory follicles were found along with fully functional vascularization which was manifested by expression of factor VIII, VEGF and SMCA. Proliferating cells were detected in follicles, and the rate of apoptosis was minimal in ovaries of control and autotransplanted ovaries. Conclusion These data demonstrate successful autotransplantation of a portion of frozen/thawed ovaries manifested by restoration of selected ovarian function including in vitro maturation of collected oocytes, presence of follicles from several stages of folliculogenesis and blood vessels expressing specific markers of vascularization, and proliferation and apoptosis of ovarian cells. Thus, heterotopic autotransplantation of a whole frozen/thawed ovary allows for development of preovulatory follicles, oocyte growth, and for restoration of vascularization and cellular function. However, additional improvements are required to enhance the efficiency of autotransplantation of frozen/thawed ovaries to produce more oocytes.